Experiences of First-Time Mother in Exclusive Breast-Feeding: A Scoping Review - Manjorang, Novita Andriani; Hidayat, Asri (Universitas Aisyah Pringsewu, 2024)
The infant mortality rate in Indonesia is now around 30 babies in every 1000 live births and around 5% of deaths are caused by infectious diseases related to low immunity in babies due to lack of breast milk intake. This scoping review aims to review the evidence base regarding the experiences of mothers in providing exclusive breastfeeding. Method: the writing structure of this scoping review uses the PRISMA-ScR Checklist according to Arksey and O'Malley with five stages. Article search uses three databases including PubMed, Wiley Online library, google scholar and sciencedirect. Inclusion criteria, the criteria included in this review, were Indonesian or English articles published in the last 5 years and articles focused on mothers' experience in providing exclusive breastfeeding. Of the 195 articles that had been searched and selected, there were 6 articles that met the inclusion criteria in this review and two themes were found, namely, knowledge and support for exclusive breastfeeding. From several articles obtained during the research, it was found that mothers experience difficulty in breastfeeding, feel anxious, and have social stigma. Despite the delay, feeding, social and psycho-social support helped mothers cope.